Mudança estratégica: o caso do setor alcooleiro - Rigon, Cleide Marisa (2004)
This research aims to understand the context, process and the content of the strategic changes which characterized the history of ALPOX, a self-managed alcohol distillery set up in Porto Xavier, a small town in the northwest of the Rio Grande do Sul State (in the south of Brazil), from 1984 to 2003. In a general way the research interprets and emphasizes the real strategic changes happened in the period mentioned above, the internal and external factors in the context that influenced it and the result got by the organization with the change implementation. In relation to the used methodology, it is an unusual case study developed through a qualitative approach (Triviños, 1992; Gil, 1999; Yin, 2001) and a contextualizing approach (Pettigrew, 1987, 1992). At the same time, it was also based on the method of historical and longitudinal analysis (Kimberly, 1976; Salama, 1992) when adopting the direct research procedures ( Mintzberg and McHugh, 1985). From the historical and interpretative analysis of the organization, it was described the main critical events occurred at the distillery and it was identified the three-strategic periods which make up the studied period. The first strategic period (1984-1990) is characterized by the implementation of the distillery in that town and the mobilization towards the whole structure of the first cane-plantations. The second one (1991-1996) signs the organization renting period as a strategy to overcome the financial crisis. And the third one (1997-2003) is marked by the strategic decision of the company s failure and the renting of the broken mass by COOPERCANA. During each strategic period it was done an analysis based on theoretical approaches aiming a better explanation about the strategic changes. The theoretical explanation made possible a more accurate comprehension about the events and their meanings attached by the organizational actors (interviewed people) and by the researcher through the perception and the parallels identification from the existing theoretical approaches about the subject. So it is emphasized as the main contributions of the present study: the strategic change discussion in an organization of the sugar-alcohol agriindustrial sector which plays an important role on the Brazilian economy as in the region it is insert; the methodology used in the research because it privileges the analysis into a historical, contextualizing and processional perspective, providing much information about the formulation process of an organization s strategies in the Brazilian context; and a critical reflection on the strategic behavior adopted throughout the history of the distillery serving as subsidies for future decisions and actions of its directors.